Knowledge, Attitudes and Practices of Adolescents, Adults and Older Adults Toward the Disease of Novel Coronavirus During its Outbreak in Matrouh, Egypt - El Refaey, Noura Mahmoud; Hassan, Seham El-Sayed Saleh; El-Sakhy, Nancy Mahmoud (International Journal For Research In Health Sciences And Nursing, 2020)
The novel coronavirus disease (COVID- 19) has become the major pathogen of merging respiratory disease outbreaks. Compliance with preventive measures is affected by populations' level of knowledge, attitudes, and practices (KAP) toward COVID- 19. Aim: The present study aimed to identify knowledge, attitudes, and practices of Adolescents, adults and older adults toward the disease of novel Coronavirus during its outbreak in Matrouh, Egypt. Design: A cross-sectional survey was utilized. Setting: The study was carried out virtually using a link of a Google form shared on social networking sites of the most popular Facebook and WhatsApp pages and groups in Matrouh governorate. Subjects: All adolescent, adults, and older adults of the general community in Matrouh, Egypt who respond to the study link during the first month of starting the partial lock down in Egypt (from the mid of March to a mid of April 2020) were recruited conveniently based on the following criteria: - aged 11 years and above, lived in Matrouh governorate and accepted to participate in the study. The sample comprised two thousand (2000) individuals. Tools: The data was collected through a survey questionnaire containing four parts, part I: Socio-demographic characteristics of participants. Part II: knowledge regarding COVID-19. Part III: Attitudes towards COVID-19. Part IV: Practices towards COVID-19. Results: The findings of the present study concluded that more than two thirds of the participants had "good" knowledge score and the majority of them had "positive" attitude score. While, more than half of the participants had "fair" practice score. Furthermore, there is a statistically significant association between different age groups and their knowledge, attitude, practice and the overall total score, where knowledge, attitude, practices and overall total scores were lowered among adolescents compared to adults and older adults. Additionally, there is a significant positive (Direct) correlation between total knowledge, attitude and practices score and overall total scores of participants. Finally, the total practice and total attitude scores of the participants were significant negative (inversed) correlated. Recommendations: The main recommendations of the current study were to raise the knowledge, attitude and practices of all populations in the Egyptian community regarding COVID- 19 and provide updated simplified Arabic posters about COVID-19 to help all populations in improving their awareness.